Loneliness in older adults - Stall, Nathan M.; Savage, Rachel D.; Rochon, Paula A. (Canadian Medical Association journal (CMAJ), 2019)
Five things to know about loneliness in older adults are presented. These are the following: 1. Loneliness is an emotional state of perceived social isolation; 2. Loneliness is common among older adults and linked to declines in health; 3. Loneliness is as harmful as other well-established risk factors for mortality; 4. Loneliness is an important contributor to use of health care; and 5. Social prescribing is an emerging intervention for loneliness.